STABILITY ANALYSIS ON LOW WALL SLOPE OF PIT A PT XYZ COAL OPEN PIT USING LIMIT EQUILIBRIUM METHOD - Durra Hibatul Wafi, Muhammad
PT XYZ is a coal mining company located in Kutai Kartanegara Regency, East Kalimantan. In this final project research, a stability analysis of the low wall life of mine (LOM) slope of Pit A PT XYZ is carried out using the boundary equilibrium method. The analysis is only conducted using dynamic equilibrium conditions. Slope stability conditions are expressed in a factor of safety index (FK). According to the provisions in the Regulation of the Minister of Energy and Mineral Resources No. 1827/K/30/MEM/2018, the minimum dynamic safety factor used is 1.1. The assumptions used in this final project research are a seismik load factor of 0.05g; tool load factor of 430 kN/m2; water conditions are assumed to be saturated with a water pore pressure value of 1. The dynamic safety factor obtained from the analysis carried out on the LOM low wall slope is 0.935 and it can be concluded that the slope is unstable and unsafe. The recommendations given in this final project research are 3 (three) recommendations with each different treatment such as cutting weak plane, applying counter weight, and/or re-sloping on the low wall overall slopes of PT XYZ's Pit A.